CRITICAL TOTAL QUALITY MANAGEMENT IN MANUFACTURING COMPANIES: A CASE STUDY IN MAKASSAR - Musran Munizu (Universitas Hayam Wuruk Perbanas, 2011)
The aim of this study was to empirically investigate the effect of critical TQM practices on operational performance of medium and large manufacturing companies in Makassar. The critical total quality management (TQM) practices divided into three factors, i.e. strategic, tactical, and operational factors as predictors of operational performance. Total of popula- tion were 143 manufacturing companies. A questionnaire designed and distributed to all population, a total of 59 returned. It consists of both 29 medium companies and 30 large companies. Data analysis use both descriptive and multiple regression analysis (MRA).The empirical analysis demonstrates several key findings: data analysis reveals that there was a positive effect of critical TQM practices which consists of strategic, tactical, and operational factors on operational performance. Tactical factors were the strongest significant predictors of operational performance. Overall, the results showed the central role of the tactical fac- tors as critical factors in improving the operational performance within medium and large companies in Makassar manufacturing industrial. There were some research limitations. For instance, the study is using perceptual data provided by production managers or quality managers which may not provide clear measures of performance